Formation of summer phytoplankton bloom in the northwestern Bay of Bengal in a coupled physical‐ecosystem model. Issue 12 (7th December 2016) - Thushara, V.; Vinayachandran, P. N.
Abstract: The Bay of Bengal (BoB) is considered to be a region of low biological productivity, owing to nutrient limitation, caused by strong salinity stratification induced by the freshwater influx from rivers and precipitation. Satellite and in situ observations, however, reveal the presence of prominent regional blooms in the bay in response to monsoonal forcings. Bloom dynamics of the BoB are presumably determined by freshwater as well as the local and remote effect of winds and remain to be explored in detail. Using a coupled physical‐ecosystem model, we have examined the oceanic processes controlling productivity in the northwestern BoB during the summer monsoon. The region exhibits a prominent bloom lasting for a period of about 2 months, supporting major fishing zones along the northeast coast of India. The ecosystem model simulates the spatial and temporal evolution of the surface bloom in good agreement with Sea‐Viewing Wide Field‐of‐View Sensor (SeaWiFS) observations. Vertical distribution of upper ocean physical and biological tracers and a nitrate budget analysis reveal the dominant role of coastal upwelling induced by alongshore winds in triggering the bloom. Horizontal advection plays a secondary role by supplying nutrients from coastal to offshore regions. The bloom decays with the weakening of winds and upwelling by the end of summer monsoon. The simulated bloom in the northwestern bay remains largely unaffected by the freshwater effects, since the peak bloom occurs before the arrival of river plumes. Key Points: Formation mechanisms of summer bloom in the northwestern Bay of Bengal are explained using a coupled physical‐ecosystem model Bloom evolution is dominantly controlled by coastal upwelling induced by alongshore winds Influence of freshwater runoff on the bloom dynamics is not significant